Recovered Voices, Newfound Questions: Family archives and historical research - Maria de Lurdes Rosa (Investigação, 2019)
The book aims at presenting less known or completly unknown family archives. It proposes to question them and to analyze them under new perspectives (both from history and archival science), in order to found the "voices" if its producers - and thus to develop new research questions. It comprises three parts: "Recovering, reconstructing and (re)discovering family and personal archives"; "From a social, political and cultural history of the families to a social history of the archives"; "Public preservation and promotion of family and personal archives".